ANALYSIS OF FACTORS AFFECTING THE EFFECTIVENESS OF DISTANCE LEARNING MODE IN THE PREPARATION OF TEACHERS IN COLLEGES OF EDUCATION, NIGERIA - M, Saba T; S, Mamman J; N, Nwabufo B (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Distance learning education has been considered as a viable tool which not only helps in solving the problem of shortage of teachers but also the high attrition rates that is often associated with study leave. It was believed that distance education has the capacity to prepare qualified teachers just as the face-to-face education mode. However, there seem to be gaps between the objectives establishing distance education and their realization. The obvious indicators to this fact are the unqualified teachers who cannot express themselves in the classroom. The study explored the factors affecting the effectiveness of distance learning mode in the preparation of teachers in Colleges of Education, Nigeria. The researcher constructed 30 questionnaire items from the literature relevant to the study. The questionnaire yielded a reliability coefficient of 0.83. A total of 151 questionnaires were administered on 38 and 113 lecturers and students of College of Education, Minna and Mokwa study centers. All the questionnaires were completed and retrieved. The study revealed that all the constructs constituted factors affecting the effectiveness of the distance learning mode of education in the preparation of teachers in Colleges of Education in Nigeria. It was concluded that the nation will continue to be in dire need of adequate qualified teachers if the factors affecting the effectiveness of the program are not eliminated. It was recommended among others that institutions establishing distance learning programs should ensure that the needed facilities for the effective running of the program are properly put in place. Facilities such as; technologies that will create an interactive learning environment even at a distance.